Bahasa Inggris - Nova Anjarwati; Ketang Wiyono; Ida Sriyanti (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to produce e-module teaching material products containing local wisdom from South Sumatra based on the theory of conceptual change that is valid, practical and effective in students' conceptual understanding. The development model used is the Rowntree development model modified with formative evaluation. The subjects in this research were class XI students at SMA 19 Negeri Palembang. Based on this data analysis, it is declared valid, practical, and effective in students' understanding of concepts. The results obtained were: the expert review stage obtained an average score from material experts of 85.71%, linguistic experts of 93.05% and appropriateness of presentation and appearance of 75.48%; the one to one stage obtained an average score of 95.11%; the small group stage obtained an average score of 95.08%. Based on the results of the field test, the N-gain calculation obtained a score of 0.64 with interpretation being seen from the test results calculating the pre-test and post-test scores. Thus, it can be concluded that using e-module teaching materials containing local wisdom based on the theory of conceptual change can improve students' conceptual understanding.